Food insecurity and its association with changes in nutritional habits among adults during the COVID-19 confinement measures in Belgium. Issue 5 (9th April 2021) - Vandevijvere, Stefanie; De Ridder, Karin; Drieskens, Sabine; Charafeddine, Rana; Berete, Finaba; Demarest, Stefaan
Abstract: Objective: To assess food insecurity and its association with changes in nutritional habits among Belgian adults during confinement due to COVID-19. Design: Three cross-sectional online health surveys were conducted during March–May 2020. Multinomial logistic regression models were used to determine associations between self-reported changes in fruit, vegetable, soft drink and sweet and salted snack consumption or weight as dependent variables and food insecurity indicators as independent variables, adjusted for gender, household composition, educational attainment and household income. Setting: Belgium. Participants: In total, 8640 adults recruited by convenience sampling. Results: About 10·4 % of Belgians often or sometimes feared food shortages, 5·0 % were often or sometimes short of food without money to buy more and 10·3 % often or sometimes could not afford to eat a healthy diet during confinement. These percentages were highest among single-parent families (26·7, 14·4 and 23·4 %, respectively). Adults who often or sometimes feared that food would run out during confinement had significantly higher odds of decreased v . unchanged fruits (3·53; 95 % CI = 2·06, 6·05) and vegetables (5·42; 95 % CI = 2·90, 10·11) consumption and significantly higher odds of increased v . unchanged soft drink consumption (3·79; 95 % CI = 2·20, 6·54). Similar results were found for adults who often or sometimes ran out of food and for adults who often or sometimes were not able to afford a healthy diet. Conclusion: Food insecurity during the COVID-19 confinement measures in Belgium was associated with adverse changes in most dietary behaviours. A strong government response is needed to tackle malnutrition and food insecurity to protect public health from ongoing and future pandemics.